Distribution of PSU Scores for Dentistry Schools in Chile during 2012-2014. - Luis Espinoza (Universidad de Concepción., 2014)
To describe distribution of applicants' scores in the University Selection Test (Prueba de Selección Universitaria, PSU) for dentistry in Chilean universities associated with the PSU test between 2012 and 2014. Methodology: A retrospective study based on the applicants' records to dentistry in universities associated with the PSU admission process from 2012 to 2014. Results: There were twenty careers, representing sixteen universities associated with the PSU process. From them, ten were private and ten traditional. Overall, 19,469 students applied and 6,105 were summoned to fill 4,828 vacancies during the period under study. There was a drop in the number of applicants per vacancy from 5.30 to 3.11 and the selection per quota rose from 1.23 to 1.32, varying mostly in private universities. The weighted average score was 662.78 ± 44.73 with a steady decline without differences regarding sex mostly in private universities. Conclusions: During 2012-2014, there were fewer candidates for dentistry, as well as lower scores primarily affecting private schools.